2012
DOI: 10.1177/0954405412437621
|View full text |Cite
|
Sign up to set email alerts
|

Integrating effect of forming in fatigue life prediction: review of present scenario and challenges

Abstract: Plastic deformation of sheet metals during forming induces complex residual stresses in the component owing to its geometry and material anisotropy. The residual stresses affect the durability of the components. Fatigue life estimation incorporating the forming-induced residual stresses is limited. In the present work, the state-of-the-art in modelling sheet metal forming, residual stress estimation and fatigue life prediction are reviewed. The challenges in integrating the residual stress owing to forming and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 125 publications
1
5
0
Order By: Relevance
“…That result is confirmed by other authors, such as Zhang et al [6]. As a consequence, the wear resistance of burnished materials is improved, which shows the comprehensive effects of burnishing as a finishing process (Hassan et al) [7], and a longer lifespan of industrial components can be expected, as explained by Hariharan and Prakash [8].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…That result is confirmed by other authors, such as Zhang et al [6]. As a consequence, the wear resistance of burnished materials is improved, which shows the comprehensive effects of burnishing as a finishing process (Hassan et al) [7], and a longer lifespan of industrial components can be expected, as explained by Hariharan and Prakash [8].…”
Section: Introductionsupporting
confidence: 78%
“…The obtained residual stresses were also corrected using Eqs. (6), 7, and (8), which take into consideration all corrections performed through the FEM. Real residual stresses deduced from those expressions have been plotted for specimen #5, and are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Besides, as known, the V-groove can induce the stress concentration effect. [8][9][10][11] The cropping time and the cropping load, which directly affect the efficiency and the energy consumption, can be greatly reduced by the stress concentration effect. Some new different lowstress bar fine-cropping methods have been proposed based on the stress concentration in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Applying uniform hydrostatic pressure during the uniaxial tensile process can improve the limit of forming properties to a certain extent. 10 The related research results showed that hydrostatic pressure has a minor effect on the constitutive relations of aluminum, aluminum alloy and copper bar. However, it has a significant effect on the fracture mechanism and ductility.…”
Section: Introductionmentioning
confidence: 99%